Surgical treatment of varicose veins - Shellito, John G.; Aytaç, Aydın (The Turkish Journal of Pediatrics, 1963)
The procedure of choice in the surgical treatment of varicose veins combines: 1. ligation of the greater saphenous vein at the saphenofemoral juncture, 2. ligation and complete stripping of the lesser saphenous vein when necessary, 3. complete stripping of the greater saphenous vein, 4. removal by stripping or dissection of involved veins. One month postoperatively, small tributary or perforating veins may be injected with sclerosing solution, if required. Injection therapy for varicose veins, or skin grafts for varicose ulcers, is not recommended prior to ligation and stripping.